THE DISCOURSES OF THE INVENTION OF THE NATIONAL CELEBRATION OF NICOYA’S ANNEXATION, 1940-1974 - Alfaro Salas, Esteban (2025)
Between 1940 and 1974, the celebration of Nicoya’s annexation had a nationwide expansion and grew as a national event, caused mainly by the growth of the Welfare State, and the official declaration of its celebration as a national holiday. In this paper, we determined the motivations for converting the annexation’s celebration into a national holiday, we established the links between this process and the regionalist discourses that existed in Guanacaste, and establish how identified was the general population of Costa Rica with the new national holiday. In order to do this, we analyzed the discourses of articles that were broadcast in some of the principal newspapers in the country, and a regional one; in which we have found the main scenarios, subjects, and arguments of this process. We found that this expansion intended first, to appease the discourses that supported the arguments that Guanacaste was the “Cinderella” of Costa Rica because it was a neglected region in economic, social and political terms. Second, the Welfare State needed physical and media tribunes to spread its support for some predominant agricultural activities in the province, and try to better position its image in the country. The sesquicentennial celebration of the annexation, in 1974, was a milestone in the deployment that this was achieved in Guanacaste, however, showed that it was still not consolidated with the desired intensity in the rest of the country.